EANO guideline on the diagnosis and treatment of vestibular schwannoma. Issue 1 (28th October 2019) - Goldbrunner, Roland; Weller, Michael; Regis, Jean; Lund-Johansen, Morten; Stavrinou, Pantelis; Reuss, David; Evans, D Gareth; Lefranc, Florence; Sallabanda, Kita; Falini, Andrea; Axon, Patrick; Sterkers, Olivier; et al.
Abstract: The level of evidence to provide treatment recommendations for vestibular schwannoma is low compared with other intracranial neoplasms. Therefore, the vestibular schwannoma task force of the European Association of Neuro-Oncology assessed the data available in the literature and composed a set of recommendations for health care professionals. The radiological diagnosis of vestibular schwannoma is made by magnetic resonance imaging. Histological verification of the diagnosis is not always required. Current treatment options include observation, surgical resection, fractionated radiotherapy, and radiosurgery. The choice of treatment depends on clinical presentation, tumor size, and expertise of the treating center. In small tumors, observation has to be weighed against radiosurgery, in large tumors surgical decompression is mandatory, potentially followed by fractionated radiotherapy or radiosurgery. Except for bevacizumab in neurofibromatosis type 2, there is no role for pharmacotherapy.